Synthesis and Characterization of Pt-Polyaniline Composite - Kumar, Neeraj (My University, 2010)
Polyaniline and Pt-polyaniline composite samples are synthesized by chemical routes. The samples are characterized by X-ray diffractometer and thermogravimetric analyzer. I-V characteristics of the sample are also studied. Results and analysis indicate for increase in conductivity of the Pt-polyaniline composite in comparison to polyaniline.
M.Tech. (Materials Science and Engineering)
Keywords: Platinum; polyaniline composite